Determination of surface waviness using radius of curvature measurement with laser scanning technique - Pieńkos, Tomasz; Gładyszewski, Longin; Proszyński, Adam; Chocyk, Dariusz; Gładyszewski, Grzegorz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A method for obtaining the shape of a surface investigated with a laser scanning curvature measurement is presented. Additional simple analysis of raw experimental data allows one to determine waviness of the sample. The accuracy of the method and comparison of the results obtained with the method and commercial profilometer are also described.
Optica Applicata, Vol. 35, 2005, nr 3, s. 503-507
Keywords: optyka; waviness; curvature; profilometer